Examining the associations between control (primary and secondary) appraisals and posttraumatic stress disorder symptoms in Malaysian and Australian trauma survivors - Reyneke, Tamsyn; Lee, Bryan; Li, James Haoxiang; Haque, Shamsul; Abdullah, Siti Zainab; Tan, Britney Kerr Wen; Liddell, Belinda; Jobson, Laura (Frontiers in Psychology, 2023)
Background: Little research has considered the influence of culture on control appraisals in the context of posttraumatic stress disorder (PTSD). Objectives: This study aimed to investigate whether cultural group moderated the relationship between control (primary and secondary) appraisals and PTSD symptoms in trauma survivors from Western (Australian) and Asian (Malaysian) cultural contexts. Method: Trauma survivors (107 Australian with European cultural heritage; 121 Malaysian with Malay, Indian or Chinese cultural heritage) completed an online survey assessing PTSD symptoms and appraisals of control. Results: Cultural group moderated the association between primary control and PTSD symptoms; the positive association was significant for the Australian group but not the Malaysian group. While cultural group did not moderate the association between secondary control and PTSD symptoms, there was an indirect pathway between secondary control appraisals and PTSD symptoms through interdependent selfconstrual for both cultural groups. Conclusions: The findings indicate that cultural group and self-construal influence the associations between different types of control appraisals and PTSD.Further research exploring the role of culture and different appraisal types in PTSD is needed.